The Future of Quail Hunting in the Southeastern United States - Frank B. Barick (National Quail Symposium Proceedings, 2017)
More than 60 years of habitat improvement efforts by state agencies has not prevented the decline of northern bobwhites (Colinus virginianus) in southeastern states, nor has ten years of habitat improvement sponsored by Quail Unlimited resulted in their restoration. Therefore, it would appear reasonable to speculate that the cause of the decline might be something other than habitat loss or degradation. Since recent research seems to also absolve most agricultural chemicals, it may be reasonable to consider some other causes. One very likely suspect is predation. This suspicion is confirmed by recent research in Oklahoma and Virginia. Also, reduction of predation on several project areas has resulted in apparent increases in quail populations. We need more research to further test this hypothesis, and the parameters of both mammalian and avian predation should be investigated. If predation is the primary factor responsible for the decline of quail, and assuming that current wildlife policy will not allow wide-scale reduction of predator populations, the future quail hunting opportunities will be limited to areas where predator reduction and control are a major component of northern bobwhite management efforts.